Ansoff’s Strategic Turbulence Model: Why It’s Important to Marketing Strategy - Kipley, Dan; Helm-Stevens, Roxanne; Skalnik, Patricia (Archives of Business Research, 2022)
The purpose of this paper is to briefly introduce the reader to Ansoffian strategy and the concepts of environmental turbulence and examine their impact on marketing strategy. The authors overlay Ansoff’s identification of turbulence levels to marketing strategy as a dynamic synergy of management processes and innovation which depends on a firm’s posturing to address marketing aggressiveness and environmental turbulence. Within the environmental turbulence model, Ansoff puts forth that the third level is where marketing becomes a critical functional activity of strategic success and where customers and competitors are factors in the environmental turbulence. Advancing to levels four and five, firms must now integrate the latest technologies and processes required to facilitate and create innovation in response to a faster-moving, dynamic, and surpriseful environment. Ansoff described the changing turbulence levels as increasing unpredictability, novelty, and complex, especially when considering movement from his level four (exploring) turbulence level to a level five (creative and “surpriseful”). When the environment shifts to the highest level of disruption-discontinuity where change is occurring faster and more surpriseful, a firm must adopt a heightened level of strategic aggressiveness into the organizational structure and rapidly adapt marketing postures and strategies to reposition the firm’s marketing mix to optimize opportunities and mitigate change threats. Through the lens of discontinuous environmental turbulence, the authors explore recent and extant research and unravel how new strategic marketing principles align with the foundational tenets of Ansoff’s strategic diagnosis and gap analysis methodology by analyzing the internal environment and comparing it to the external environment. Additionally, the researchers explore how the greater the “gap” between capabilities and marketing strategy, the more the firm needs to perform a realignment of itself to mitigate the impending effects of the environmental turbulence pressures.